Interpersonal Metadiscourse pada Tagline Iklan Poster World Wildlife Fund (WWF) - Bayu Permana Sukma (PAROLE: Journal of Linguistics and Education, 2013)
This article describes types and functions of interpersonal metadiscourse in printed advertisement tagline. The three types, i.e. person marker, hedges, and emphatics have various roles in interpreting properly tagline meaning. The writer uses Hyland’s metadiscourse theory, Fuertes-Olivera et al’s interpersonal discourse in slogans, and Halliday’s functional grammar to analyze the data. The data were collected from printed advertisements by World Wildlife Fund (WWF). The result shows that each of the interpersonal metadiscourse features has different functions. Person marker is used to show the writer’s position in a text, hedges is used to imply the writer’s opinion, while emphatics serves as a device to convince the readers that the messages given in the text are true.   Artikel ini mendeskripsikan jenis dan fungsi ‘interpersonal metadiscourse’ yang tercetak di ‘tagline’ iklan. Ketiga jenis, yaitu penanda orang, pemagaran, dan penegasan mempunyai berbagai peranan untuk menafsirkan makna tagline secara tepat. Penulis menggunakan teori ‘metadiscourse’ (Hyland), ‘interpersonal discourse’ dalam slogan (Fuertes-Olivera dkk.), dan ‘functional grammar’ (Halliday) untuk menganalisis data. Data dikumpulkan dari beberapa iklan cetak ‘World Wild Fund’ (WWF). Hasil penelitian menunjukkan bahwa setiap jenis memiliki fungsi yang berbeda. Penanda orang digunakan untuk menunjukkan posisi penulis dalam sebuah teks, pemagaran digunakan untuk menyatakan secara tidak langsung pendapat penulis, sementara penegasan berfungsi sebagai alat untuk meyakinkan pembaca bahwa pesan yang diberikan dalam teks benar.